Crosstalk in stereoscopic displays - Woods, Andrew J. (Curtin University, 2013)
Crosstalk is an important image quality attribute of stereoscopic 3D displays. The research presented in this thesis examines the presence, mechanisms, simulation, and reduction of crosstalk for a selection of stereoscopic display technologies. High levels of crosstalk degrade the perceived quality of stereoscopic displays hence it is important to minimise crosstalk. This thesis provides new insights which are critical to a detailed understanding of crosstalk and consequently to the development of effective crosstalk reduction techniques.